Kinetics of odorant compounds in wine brandies aged in different systems - Caldeira, Ilda (2016)
The odorants compounds of aged wine brandies comprise compounds deriving from the wood, from the distillate and from the reactions that occur inside the barrel. The aim of this work was to study the kinetics of the odorant compounds of a wine brandy during two years of ageing in two ageing systems. The odorant compounds in the analysed brandies changed significantly over the time, but with different evolution patterns. The wood related compounds increased over time, with the highest increase in the first months of ageing. The kinetics of cis, trans-b-methyl-c-octalactone, acetovanillone and of seven volatile phenols are established for the first time in brandies. Moreover, a significant effect of the ageing system was found on the kinetics of the wood related compounds. These results pointed out the interest of these compounds as a tool to discriminate different ageing technologies